Restructuring of the Rural Economy in Ukraine: Undergoing Processes and New Directions - Vitaliy Krupin (Wieś i Rolnictwo)
The article is devoted to a review and analysis of restructuring in the rural economy of Ukraine in the past 25 years, being the years of the country’s independence. The main issues have been noted, one of the most influential being the chaotic and unregulated development – based not on thought-through policies, but on the urge of various business groups to achieve high incomes and control over the market, leaving most of the rural inhabitants without proper support and with underdeveloped infrastructure. The main changes in the 1990s and 2000s have been reviewed with the focus on their influence upon the rural economy. Agricultural production indicators have been analysed, including the structure of areas under crops, changes in the production of main agricultural crops, quantity of livestock, including poultry, as well as economic issues, such as incomes in the sector. Vast analysis is given of factors which influence the undergoing processes in Ukrainian rural economy (in particular the state agricultural support system and quality of reforms in agriculture), as well as local endogenous factors (reluctance of rural inhabitants to develop and take personal initiative).